ҚАРАҚАЛПАҚ ТИЛИНДЕ ҚОСПА АТЛЫҚЛАРДЫҢ ИЗЕРТЛЕНИЎИ - Опаева, Р. (FAN va JAMIYAT, 2018)
The article is devoted to the issues of such way of word formation as word composition in the Karakalpak language, to the study of compound nouns, in particular. The author analyzed the theoretical points of view of the famous scholars devoted to the study of word composition, compound houns, in particular.